Morphology Analysis of GNS and GNS/Al2O3 Composites - Wang, Jing; Zhang, Jin; Liu, Zhenying (Asian Journal of Chemistry, 2013)
Graphene sheets have been emerging as a fascinating material with its many unique properties. So the introduction of GNS into ceramic composites will be a tantalizing foreground. GNS was prepared by redox method in this study and tested by SEM of GNS was ultrasonic dispersed with different time. From the experimental results, GNS of ultrasonic dispersing with 6 h is the best and it presents slice attached to matrix. GNS/Al2O3 composites was prepared by in situ coating process and tested by TEM, and the precursor is good dispersion.